Monitoring of resistance genes in Listeria monocytogenes isolates and their presence in the extracellular DNA of biofilms: a case study from the Czech Republic - Boháčová, Martina; Zdeňková, Kamila; Tomáštíková, Zuzana; Švarcová, Viviana; Demnerová, Kateřina; Karpíšková, Renáta; Pazlarová, Jarmila (Folia microbiologica, 2018)
The alarming occurrence of antibiotic resistance genes in food production demands continuous monitoring worldwide. One reservoir of resistance genes is thought to be eDNA. There is currently little available information in Europe about either the extracellular DNA distribution of the bacterium or the spread of resistance genes in L. monocytogenes. Therefore, our aims were to give insight into the Listeria monocytogenes resistance situation in the Czech Republic and assess the presence of resistance genes in their extracellular DNA (eDNA). First, susceptibility tests were performed on 49 isolates of L. monocytogenes with selected antibiotics. Next, we tested DNA of suspected isolates for the presence of resistance genes in both planktonic cells and the eDNA of biofilms. Finally, fluorescent confocal microscopy was used to observe the eDNA pattern of selected isolates under conditions that mimicked the food processing environment and the human body. Susceptibility tests found isolates intermediate resistant to chloramphenicol, tetracycline, and ciprofloxacin as well as isolates resistant to ciprofloxacin. For all suspected isolates, PCR confirmed the presence of the gene lde encoding efflux pump in both types of DNA. When the biofilm was observed using confocal laser scanning microscope, the eDNA distribution patterns varied considerably according to the culture conditions. Furthermore, the food and clinical isolates varied in terms of the amount of eDNA detected. The presence of an efflux pump in both types of DNA suggests that the eDNA might serve as a reservoir of resistance genes. Surprising differences were observed in the eDNA pattern. Our results suggest that the current risk of the spread of L. monocytogenes resistance genes is low in the Czech Republic, but they also indicate the need for continuous long-term monitoring of the situation.
Keywords: Cluster Analysis; extracelulární prostor; Extracellular Space; Česká republika; Listeria monocytogenes; Microbial Sensitivity Tests; Drug Resistance, Bacterial; Genes, Bacterial; potravinářská mikrobiologie; lidé; Czech Republic; DNA bakterií; shluková analýza; mikrobiální viabilita; DNA, Bacterial; bakteriální léková rezistence; Anti-Bacterial Agents; Microbial Viability; biofilmy; mikrobiální testy citlivosti; Humans; Biofilms; antibakteriální látky; Food Microbiology; bakteriální geny